Constructing a Model for Domain-specific Risk-taking, Life Satisfaction and Risk Tolerance of Investors - Dickason-Koekemoer, Zandri; Sune Ferreira-Schenk (International Journal of Economics and Financial Issues, 2022)
Research within investment companies is necessary to assist financial planners to accurately identify the factors that may influence their client’s financial risk tolerance and ultimately the performance of their portfolios. Therefore, the objective of this paper is to identify whether factors such as investor personality and life satisfaction influence an investors risk tolerance level. An electronic survey was utilised where the responses were collected from the clientele (1 065) of a private investment firm in South Africa. Results indicated that life satisfaction was found to significantly contribute to predicting investor risk tolerance. The financial, social and recreational, domains of an investors personality also had a significant influence on risk tolerance. The development of this risk tolerance SEM is unique in its existence, as it is the first to model life satisfaction, risk perception and the risk tolerance level of private investors in South African. As a result, these findings will make a significant contribution to the way financial investment companies profile their clients.